Methotrexate versus mycophenolate mofetil prophylaxis in allogeneic hematopoietic cell transplantation for chronic myeloid malignancies: a retrospective analysis on behalf of the chronic malignancies working party of the EBMT - Luft, Thomas; Gras, Luuk; Koster, Linda; Kröger, Nicolaus; Schröder, Thomas; Platzbecker, Uwe; Sockel, Katja; de Latour, Régis Peffault; Stelljes, Matthias; Sengeloev, Henrik; Eder, Matthias; Blau, Igor Wolfgang; et al. (American journal of hematology, 2025)
Prophylaxis strategies for Graft versus host disease (GVHD) in allogeneic hematopoietic cell transplantation (allo-HCT) frequently encompass a combination of a calcineurin inhibitor (CNI) with either methotrexate (MTX) or mycophenolate mofetil (MMF). The aim of this retrospective, EBMT registry-based study was to determine outcome differences for chronic myeloid malignancies and secondary acute myeloid leukemia (sAML) between MTX- and MMF-based prophylaxis regimens while taking potential heterogeneity between subgroups into consideration. Eligible were patients transplanted between 2007 and 2017 who received either MTX- or MMF prophylaxis in combination with a CNI. Endpoints after allo-HCT were overall survival, relapse-free survival (RFS), relapse incidence, non-relapse mortality (NRM), and Grades 2-4 acute GVHD (aGvHD). Overall, 13 699 patients from 321 centers were included. Median follow-up was 42.8 months (IQR 19.8-74.5 months). MTX prophylaxis was associated with reduced overall mortality (HR 0.87, 95% CI 0.81-0.95, p = 0.001) and NRM (HR 0.86, 95% CI 0.78-0.96, p = 0.006) compared with MMF in multivariable Cox regression models in the whole cohort without significant interaction between prophylaxis and subgroups. In contrast, there was no significant association of prophylaxis with risk of relapse (HR 1.03 MTX vs. MMF, 95% CI 0.94-1.14, p = 0.53) or RFS (HR 0.95, 95% CI 0.88-1.01, p = 0.12). There was a reduced risk of Grades 2-4 acute GVHD and reduced mortality after acute GVHD with MTX prophylaxis but no association with outcome in a landmark analysis in patients without aGvHD at 3 months after allo-HCT. In conclusion, MTX-complemented CNI prophylaxis was associated with favorable survival, and with favorable survival after aGVHD compared with MMF.
Online veröffentlicht: 28 November 2024
Gesehen am 10.07.2025